STATIC RESERVOIR MODELLING OF SIHAPAS GROUP SANDSTONE KSK FIELD, CENTRAL SUMATRA - Nurdiana, Indra
KSK Field is one of the oil-producing fields in Central Sumatra Basin. Reservoirs in this field are reservoir A, B, C, and D of Sihapas Group sandstones. At present this field requires the development of additional well and steam injection to increase production. The initial step prior to development planning is static reservoir modeling that is performed to determine the geometry and distribution of reservoir properties, as well as the type of fluid in it. The study was conducted by analyzing rock facies, petrophysical analysis, seismic analysis and static reservoir modelling. The final result obtained in the static reservoir modeling is in place hydrocarbon reserves of KSK Field property distribution patterns, and also rock facies of the reservoir. Reservoir in the KSK Field is part of the Sihapas Group, that is deposited in shelf to estuarine environments. Facies rocks in the KSK Field are shoreface sandstone facies, inlet channel sandstone facies, and shelf mud facies rocks. Based on the calculation of petrophysical and laboratory analysis of reservoir, porosity in the Field KSK is more than 15%, with more than 100 mD of permeability. Based on the modelling conducted, the main reservoir sandstones in the KSK Field is Sihapas Group sandstone, consists of four layers sandstone that can be modelled into a single reservoir zone, but inserted by mudstone (shale within the reservoir). Distribution of rock property on KSK Field reservoir shown variation that is connected with the rock fasies. Contact of water with oil in this field is at depth of -438 TVDSS, and the oil reserves in place at the Field KSK is 55.239 million STB.